Chemical Synthesis, Efficacy, and Safety of Antimalarial Hybrid Drug Comprising of Sarcosine and Aniline Pharmacophores as Scaffolds - Jean Baptiste Niyibizi; Peter G. Kirira; Francis T. Kimani; Fiona Oyatsi; Joseph K. Ng’ang’a (Journal of Tropical Medicine)
Malaria is a disease caused by protozoans transmitted to humans by infected female Anopheles mosquitoes. According to the WHO report of 2015, there were 214 million cases of malaria with 438,000 deaths worldwide. Ninety percent of world’s malaria cases occur in Africa, where the disease is recognized as a serious impediment to economic and social development. Despite advancement in malaria research, the disease continues to be a global problem, especially in developing countries. Currently, there is no effective vaccine for malaria control. In addition, although there are effective drugs for treatment of malaria, this could be lost to the drug resistance in different Plasmodium species. The most lethal form is caused by P. falciparum which has developed resistance to many chemotherapeutic agents and possibly to the current drugs of choice. Reducing the impact of malaria is a key to achieving the sustainable development goals which are geared toward combating the disease. Covalent bitherapy is a rational and logical way of drug design which entails joining a couple of molecules with individual intrinsic action into a unique agent, hence packaging dual activity into one hybrid. This suggests the need to develop new antimalarial drugs that are effective against malaria parasites based on the new mode of action, molecular targets, and chemical structures. In silico studies have shown that sarcosine is able to bind to unique plasmodia proteins (P. falciparum ATCase), whereas aniline can be a ligand to target protein (enoyl acyl carrier protein reductase), hence suppressing the progression of the disease. The main objective of this study was to synthesize and determine the efficacy and safety of antiplasmodial hybrid drug comprising the sarcosine and aniline derivative for management of plasmodial infections. The hybrid drug was synthesized by adding thionyl chloride to sarcosine to form acyl chloride which was then added to aniline to form sarcosine-aniline hybrid molecule. The IC50 of sarcosine-aniline hybrid was 44.80 ± 4.70 ng/ml compared with that of aniline derivative which was 22.86 ± 1.26 ng/ml. The IC50 of control drugs was 2.63 ± 0.38 ng/ml and 5.69 ± 0.39 ng/ml for artesunate and chloroquine, respectively. There was a significant difference between IC50 of sarcosine-aniline hybrid and aniline derivative (p<0.05). There was also a significant difference between sarcosine-aniline hybrid and standard drugs used to treat malaria including artesunate and chloroquine (p<0.05). The ED50 of sarcosine-aniline hybrid drug was 6.49 mg/kg compared with that of aniline derivative which was 3.61 mg/kg. The ED50 of control drugs was 3.56 mg/kg, 2.94 mg/kg, and 1.78 mg/kg for artesunate-aniline hybrid, artesunate, and chloroquine, respectively. There was a significant difference (p<0.05) between ED50 of sarcosine-aniline hybrid and both controls such as aniline derivative, artesunate, artesunate-aniline hybrid, and chloroquine. Cytotoxicity results revealed that sarcosine-aniline hybrid was safe to vero cells with a CC50 of 50.18 ± 3.53 μg/ml. Sarcosine-aniline hybrid was significantly less toxic compared with artesunate, chloroquine, and doxorubicin. Sarcosine-aniline hybrid was efficacious and safe to mice. Therefore, covalent bitherapy should be used in drug development for drug resistance mitigation.